(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Epidemic parotitis (lat. parotitis epidemica, fever disease) is an acute infectious disease caused by a paramyxovirus characterized by non-purulent damage to glands (salivary glands, pancreas, testicles) and the central nervous system. Information about kick disease